Hubungan Antara Kedekatan Ibu dan Anak dengan Perilaku Psikososial Anak Usia Prasekolah - Sholaita, Khana; Lusmilasari, Lely; Haryanti, Fitri (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2024)
Background: Preschool age is at risk of experiencing psychosocial behavior problems which, if not treated immediately, will have an impact on development. The closeness of mother and child is basic in emotional development and social relationships. Objective: Knowing the relationship between mother and child closeness and the psychosocial behavior of preschool childrenMethod: This research is a descriptive analytical research with a research design cross sectional which will be carried out in April – June 2022 in Sleman Regency, Yogyakarta. The research involved 118 respondents taken through the method consecutive sampling. Instrument Child Parent Relationship Scale (C-PRS) is used to measure the closeness of mother and child and Preschool Pediatric Symptom Checklist (PPSC) to measure children's psychosocial behavior. Data were analyzed using correlation tests Spearman.Results: 78% of preschool children's psychosocial behavior is normal, and 22% are at risk of experiencing psychosocial problems. The most common psychosocial problems are internalization and attention problems. Mark mean The warm dimension of closeness between mother and child is higher than the conflict dimension. The warm dimension was negatively correlated with the risk of psychosocial behavior problems (r = -0,190; p = 0,039) while the conflict dimension is positively correlated with the risk of psychosocial problems (r = 0,410; p = 0,000). Conclusion: There is a relationship between the closeness of mother and child and the psychosocial behavior of preschool children. Warm mother-child closeness reduces the risk of psychosocial behavior problems. The closeness between mother and child that tends to be negative (conflict) increases the risk of psychosocial behavior problems.INTISARILatar belakang: Usia prasekolah berisiko mengalami masalah perilaku psikososial yang apabila tidak segera ditangani akan berdampak pada perkembangan. Kedekatan ibu dan anak menjadi hal dasar dalam perkembangan emosional dan hubungan sosial.  Tujuan: Mengetahui hubungan antara kedekatan ibu dan anak dengan perilaku psikososial anak prasekolahMetode: Penelitian ini merupakan penelitian deskriptif analitik dengan rancangan penelitian cross sectional yang dilakukan pada April – Juni 2022 di Kabupaten Sleman, Yogyakarta. Penelitian melibatkan 118 responden diambil melalui metode consecutive sampling. Instrumen Child Parent Relationship Scale (C-PRS) dipakai untuk mengukur kedekatan ibu dan anak dan Preschool Pediatric Symtomp Checklist (PPSC) untuk mengukur perilaku psikososial anak. Data dianalisis dengan uji korelasi Spearman.Hasil: Perilaku psikososial anak prasekolah 78% normal, dan 22% berisiko mengalami masalah psikososial. Masalah psikososial yang paling banyak adalah internalisasi dan masalah perhatian. Nilai mean kedekatan ibu dan anak dimensi hangat lebih tinggi dari pada dimensi konflik. Dimensi hangat berkorelasi negatif dengan risiko masalah perilaku psikososial (r = -0,190; p=0,039) sedangkan dimensi konflik berkorelasi positif dengan risiko masalah psikososial (r = 0,410; p = 0,000). Simpulan: Terdapat hubungan antara kedekatan ibu dan anak dengan perilaku psikososial anak prasekolah. Kedekatan ibu dan anak yang hangat menurunkan risiko masalah perilaku psikososial. Kedekatan ibu dan anak yang cenderung negatif (konflik) meningkatkan risiko masalah perilaku psikososial.